Influence of physical activities on stress reduction among Third Age University students - Svatava Nováková; Marie Blahutková; Marta Muchová; Hana Lepková (Jan Długosz University in Częstochowa, 2019)
The aim of our paper was to identify the effect of physical activities on the reduction of stress among the elderly who regularly participated in a physical activity program and point out the positive effects of these exercises. The research sample consisted of a total of 202 elderly people from 64 to 78 years of age. 102 of them regularly exercised within the framework of the Motion studio program for the elderly organised by the University of the Third Age at Brno University of Technology. Other 100 seniors did not study and none of them exercised regularly. The level of stress was measured with the Stress Test (Selye, 1993, Křivohlavý, 2001).We looked for differences in the level of stress among seniors who exercise on a regular basis and those who do not exercise. We compared age, retirement time and all physiological stress-related difficulties. We used the Pearson correlation coefficient and the factual evaluation for statistical evaluation of the obtained data. The obtained results, indicate that the seniors who came regularly to the Motion studio showed less stress than the rest of the tested elders. They showed lower level in the zone of moderate stress, on average 4.5 points (men exhibited slightly higher stress level - 5 points - than women - 4 points) compared to the average of 8.1 points among seniors without sports and regular exercise (again, men showed higher levels of stress - 8.3 points - than women - 7.9 points). We found that the time spent in retirement does not statistically significantly affect the level of stress among the elderly (0.05 % significance level). The results indicated that the main stressors in old age are primarily physiological factors, which determine the level of life quality and often cause protracted diseases, particularly those related to musculoskeletal system. The time spent in retirement does not statistically significantly affect the level of stress of the elderly. Seniors without sports and regular exercise who reported higher levels of stress complained more about their cardiovascular condition, loss of appetite and neurological problems. The research has shown that seniors who are regularly engaged in physical activities are less stressed than seniors without sports and regular exercise.